Réponses

2014-10-20T20:37:02+02:00


1) Développer et réduire :

A = (3x - 4)² + (3x - 4) (2 - 5x)

A = 9x² - 24x + 16 + 6x - 15x² - 8 - 20x

A = - 8x² - 38x + 8


2) Calculer pour x = -2 :

A = (3x - 4)² + (3x - 4) (2 - 5x)

A = (3 × -2 - 4)² + (3 × -2 - 4) × (2 - 5 × -2)

A = (-6 - 4)² + (-6 - 4) × (2 - (-10))

A = -10² + (-10) × (2 + 10)

A = -10² - 10 × 12

A = -100 - 120

A = -220


3) Résoudre l'équation (3x - 4) (-2x - 2) = 0 :

(3x - 4) (-2x - 2) = 0

-6x² - 6x - 8x - 8 = 0

-6x² - 14x - 8 = 0

-6x² - 14x - 8 + 8 = 0 + 8

-6x² - 14x = 8

x = -1